Relationship between Knowledge, Attitude and Practice of Studentâs Personal Hygiene with Scabies Incidence in Pesantren Darul Fatwa, Jatinangor, West Java, Indonesia - Purnama, Karinna Dwi; Sjambas, Dedi Rachmadi; Suwarsa, Oki (Althea Medical Journal, 2017)
Background: Scabies is a parasitic infection caused by Sarcoptesscabiei Hominis varian and Acarina order. Sarcoptes scabiei infects both male and female in any age groups, ethnics, and socio-economic levels. Transmission of scabies can pass through by a direct contact from skin-to-skin or indirect contact through sharing bed, clothes, and towels. Pesantren as an educational institution supplies facilities that are shared thus making students susceptible to scabies infection. This study was conducted to discoverrelationshipbetween knowledge, attitude, and practice of studentâs personal hygiene with scabies incidence.Methods: An analytic observational study was conducted from October to November 2015 in Pesantren Darul Fatwa, Jatinangor. Study was conducted with cross-sectional design and total sampling for the sample size. Total of 37 students whoparticipated in this study were 22 malesand 15 females. This study was begun with a stand alone-questionnaire, fill out on knowledge, attitude, and practice of personal hygiene that was supervised by researcher, and physical examination for scabies diagnosis that was performed by doctors.Results: Based on history taking and physical examination, 15 out of 37 students were diagnosed with scabies positive. All of them were males, dominated by 13 year old students, 1st and 2nd Junior High School students. Statistical analysis with chi-square test showed that there were no relationship between knowledge, attitude and practice of studentâs personal hygiene withÂ scabies incidence.Conclusions: There is no relationship between knowledge, attitude and practice of studentâs personal hygiene withÂ scabies incidence in Pesantren